2004
DOI: 10.1002/j.0022-0337.2004.68.10.tb03851.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Curriculum Implementation at North American Dental Schools

Abstract: Electronic curriculum, or E-curriculum, refers to computer-based learning including educational materials available on CD or DVD, online courses, electronic mechanisms to search the literature, email, and various applications of instructional technology including providing laptops to students, multimedia projection systems, and Internet-compatible classrooms. In spite of enthusiasm about the potential for E-curriculum to enhance dental education, there is minimal guidance in the literature to assist schools wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 18 publications
1
43
0
2
Order By: Relevance
“…22,23 A recent sur vey of electronic curriculum imple mentation at 66 North American dental schools found that e-curricu lum implementation in these schools was following a classic innovation pat tern, with a few institutions rapidly implementing while the majority made modifi cations slowly. 24 In the United Kingdom, a review of the attitudes of undergraduates and staff to the use of electronic learning found that e-teach ing was accepted more by students than by staff and that some departments were unwilling to put learning mate rial online, even if it was password pro tected. 25 One of the conclusions from the DentEd 1 project was that very few den tal schools have introduced established ICT departments or have allocated staff to ICT teaching and research.…”
Section: Barriers To Change In Dental Educationmentioning
confidence: 99%
“…22,23 A recent sur vey of electronic curriculum imple mentation at 66 North American dental schools found that e-curricu lum implementation in these schools was following a classic innovation pat tern, with a few institutions rapidly implementing while the majority made modifi cations slowly. 24 In the United Kingdom, a review of the attitudes of undergraduates and staff to the use of electronic learning found that e-teach ing was accepted more by students than by staff and that some departments were unwilling to put learning mate rial online, even if it was password pro tected. 25 One of the conclusions from the DentEd 1 project was that very few den tal schools have introduced established ICT departments or have allocated staff to ICT teaching and research.…”
Section: Barriers To Change In Dental Educationmentioning
confidence: 99%
“…Dental education is no exception to this rule [4]. With the advances in computer science, and the availability of high-speed Internet and smartphones, many universities worldwide have debuted long-distance webbased learning or multi-media instruction programs [5]. Electronic learning is growing fast worldwide, and is gaining increasing popularity among learners and mentors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past for a few decades, the students always received information from teachers in the traditional class time [1]. As the information and communication technologies such as smart phones and laptops developed rapidlly which have resulted in e-learning becoming some part of higher education in many fields [2][3]. There are a lot of potentials for reasonably combining e-learning and face-to-face teaching into structured learning environments [4].…”
Section: Introductionmentioning
confidence: 99%